Rediseño de la sede de la “Unidad Educativa Alberto Enríquez” con visión del método Montessori, Atuntaqui, Antonio Ante - Ipiales Apuango, Mariana de Jesús (2023)
This degree project will solve the general objective of redesigning the headquarters of the 'Unidad Educativa Alberto Enriquez' (UEAE), where early education works, using the Montessori educational method according to children of 3 and 4 years old, to integrate activities of the area to early education. Lately Montessori education has become popular in Ecuador, but this educational method has been applied in private education, that is why the project seeks to be inserted in public education, where children 3 and 4 years old can access a free Montessori education with spaces that allow their development. The spaces of this school allow the free exploration of the child. The redesign is proposed in the first building of the 'Alberto Enriquez' Educational Unit, where the initial education functions, after an analysis of its infrastructure and spaces through Montessori aspects found in the theoretical framework. The proposal contains spaces that allow children to feel at home, in addition to exploration areas as indicated in the analysis of references. The proposal is based on modular architecture with a village concept. In order to reach this design, a participatory free drawing workshop was also carried out to learn about the children's interests with respect to their educational establishment.